Gonadotropin-releasing hormone-like receptor 2 inversely regulates somatic proteostasis and reproduction in Caenorhabditis elegans - Kishner, Mor; Habaz, Libat; Meshnik, Lana; Meidan, Tomer Dvir; Polonsky, Alexandra; Ben-Zvi, Anat (Frontiers in Cell and Developmental Biology, 2022)
The quality control machinery regulates the cellular proteome to ensure proper protein homeostasis (proteostasis). In Caenorhabditis elegans, quality control networks are downregulated cell-nonautonomously by the gonadal longevity pathway or metabolic signaling at the onset of reproduction. However, how signals are mediated between the gonad and the somatic tissues is not known. Gonadotropin-releasing hormone (GnRH)-like signaling functions in the interplay between development and reproduction and have conserved roles in regulating reproduction, metabolism, and stress. We, therefore, asked whether GnRH-like signaling is involved in proteostasis collapse at the onset of reproduction. Here, we examine whether C. elegans orthologues of GnRH receptors modulate heat shock survival. We find that gnrr-2 is required for proteostasis remodeling in different somatic tissues during the transition to adulthood. We show that gnrr-2 likely functions in neurons downstream of the gonad in the gonadal-longevity pathway and modulate the somatic regulation of transcription factors HSF-1, DAF-16, and PQM-1. In parallel, gnrr-2 modulates egg-laying rates, vitellogenin production, and thus reproductive capacity. Taken together, our data suggest that gnrr-2 plays a GnRH-associated role, mediating the cross-talk between the reproduction system and the soma in the decision to commit to reproduction.